Women in Wine : can principles turn a profit? - Ndaba, Zanele; Hobbs, Jacklynne (London : Wits Business School, 2017)
In October 2016, the management team of Women in Wine - South Africa's first wine brand to be owned and controlled by black women - gathered to prepare for the annual meeting of company shareholders. Operating conditions locally and abroad over the preceding year had once again proved extremely challenging, and chief executive officer (CEO) Beverly Farmer felt the firm needed decisive action to improve its fortunes. Accordingly, she was going to present two possible courses of action to shareholders: focus resources on developing a more innovative marketing strategy for the company, or acquire a property to enable diversification into hospitality and farming ventures. Farmer wondered which option would be most effective in enabling Women in Wine to fulfil its central purpose: giving black women - particularly farm workers - a meaningful stake in a sector that had traditionally been controlled by white men.
Originally published in Ndaba, Z., & Hobbs, J. (2017). Women in wine: Can principles turn a profit? WBS-2017-2. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Farmer, Bev; Women in Wine; Women in the wine industry -- South Africa